Postmodern impacts on the consumption patterns, activities and theories - Batı, Uğur (Marmara İletişim Dergisi, 2008)
This paper investigated the postmodernist notion of consumption and attempts to identify some of the concerns raised by postmodern. The study proposes a methodology based on showing sample case advertisements and consumption forms for the revealing postmodern impacts on consumption and for interpreting the meaning and understanding the structure of such consumption forms. In the research, it’s stated that from the postmodern perspective on consumption, hyperreality, fragmentation, decentring of the subject, commodification of nostalgia and brand community forms are essential characteristics. However, it’s reveal that this subject is highly comprehensive and the evaluation of the conclusions would be a subject for a wider and more comprehensive study.